A new species of Peritassa (Celastraceae) from Espírito Santo, Brazil - Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2021)
Peritassa formidolosa, the new species here described, differs from other species of Peritassa Miers by its unique combination of characters: anthers dehiscent by longitudinal slits, inconspicuous connectives, and campanuliform flowers. This new taxon is included into Peritassa because of these characteristics: anther dehiscence mode and short-tubular disc free from the ovary wall.
Keywords: Atlantic forest; Hippocrateaceae; Salacioideae